Conditioned pain modulation in patients with nonspecific chronic back pain with chronic local pain, chronic widespread pain, and fibromyalgia - Gerhardt, Andreas; Eich, Wolfgang; Treede, Rolf-Detlef; Tesarz, Jonas (Pain, 2017)
Findings considering conditioned pain modulation (CPM) in chronic back pain (CBP) are contradictory. This might be because many patients with CBP report pain in further areas of the body, and altered CPM might influence spatial extent of pain rather than CBP per se. Therefore, we compared CPM in patients with CBP with different pain extent. Patients with fibromyalgia syndrome (FMS), for whom CPM impairment is reported most consistently, were measured for comparison. Based on clinical evaluation and pain drawings, patients were categorized into chronic local back pain (CLP; n = 53), chronic widespread back pain (CWP; n = 32), and FMS (n = 92). Conditioned pain modulation was measured by the difference in pressure pain threshold (test stimuli) at the lower back before and after tonic heat pain (conditioning stimulus). We also measured psychosocial variables. Pressure pain threshold was significantly increased in CLP patients after tonic heat pain (P < 0.001) indicating induction of CPM. Conditioned pain modulation in CLP was significantly higher than that in CWP and FMS (P < 0.001), but CPM in CWP and FMS did not differ. Interestingly, a higher number of painful areas (0-10) were associated with lower CPM (r = 0.346, P = 0.001) in CBP but not in FMS (r = −0.013, P = 0.903). Anxiety and depression were more pronounced in FMS than in CLP or CWP (P values <0.01). Our findings suggest that CPM dysfunction is associated with CWP and not with FMS as suggested previously. FMS seems to differ from CWP without FMS by higher psychosocial burden. Moreover, patients with CBP should be stratified into CLP and CWP, and centrally acting treatments targeting endogenous pain inhibition seem to be more indicated the higher the pain extent.
Gesehen am 07.05.2018